Maternal Cigarette Smoking and Cleft Lip and Palate: A Systematic Review and Meta-Analysis. (September 2022) - Fell, Matthew; Dack, Kyle; Chummun, Shaheel; Sandy, Jonathan; Wren, Yvonne; Lewis, Sarah
Objectives : A systematic review and meta-analysis to determine the association between active maternal smoking and cleft lip and palate etiology. Data sources : Medline, Embase, Web of Science and the Cochrane Library from inception to November, 2020. Study selection : Observational studies of cigarette smoking habits in pregnant women. Outcomes included cleft lip and/or palate, cleft lip ± palate and cleft palate only. Data analysis : Publication bias analyses were performed and the Newcastle Ottawa scales were used to assess study quality. Fixed or random effect models were used in the meta-analysis, dependent on risk of statistical heterogeneity. Results : Forty-five studies were eligible for inclusion of which 11 were cohort and 34 were case–control studies. Sixteen studies were of sufficient standard for inclusion in the meta-analysis. The summary odds ratio for the association between smoking and cleft lip and/or palate was 1.42 (95%CI 1.27-1.59) with a population attributable fraction of 4% (95%CI 3%-5%). There was limited evidence to show a dose–response effect of smoking. Conclusions : This review reports a moderate association between maternal smoking and orofacial cleft but the overall quality of the conventional observational studies included was poor. There is a need for high quality and novel research strategies to further define the role of smoking in the etiology of cleft lip and palate.